Enhancement of Diagnostic Accuracy in Endometrial Carcinoma using CW-THz Spectroscopy - Umadevi K.; Sundeep D.; Latha A.M.; Kumari S.; Varadharaj E.K.; Sastry C.C.; Vighnesh A.R.; Ali M.I.; Krishna A.G. (My University, 2025)
Background and Objective: Terahertz (THz) spectroscopy has emerged as a cutting-edge tool for advancing cancer imaging research. The objective of this study was to utilize an advanced high-resolution continuous-wave terahertz (CW-THz) imaging system to ex vivo image human endometrial cancer (EC) on unstained, formalin-fixed, and paraffin-embedded histopathology slides. The aim was to localize EC and distinguish cancerous EC tissue from the surrounding noncancerous myometrial tissue. Materials and Methods: An advanced high-resolution continuous-wave terahertz (CW-THz) imaging system was employed to image ex vivo human endometrial cancer (EC) on unstained, formalin-fixed, and paraffin-embedded histopathology slides. The terahertz spectroscopy data were meticulously processed to generate 2-D transmission THz raw images. Sophisticated image processing techniques, including Gaussian filtering and resolution enhancement, were applied to improve image clarity. Results: The resulting THz images revealed a notable increase in terahertz absorption within the EC tissue compared to the surrounding myometrium. The enhanced contrast provided by the CW-THz imaging system was pivotal for delineating tumor boundaries, closely corroborating with histopathological results. The sophisticated image processing techniques significantly enhanced image clarity, facilitating the precise localization of EC. Conclusions: This study demonstrates the promise of THz spectroscopy as a significant adjunct in cancer research, particularly in the diagnostic precision of endometrial endometrioid carcinoma. The high-resolution CW-THz imaging system effectively differentiated cancerous EC tissue from noncancerous myometrial tissue, suggesting its potential for improving diagnostic accuracy in clinical practice. © The Author(s) under exclusive licence to Association of Gynecologic Oncologists of India 2024.